Взаимодействие распыленных и карбонильных порошков железа с модельными растворами тканевой жидкости - Иващенко, Е.А.; Бошицкая, Н.В.; Проценко, Л.С.; Будылина, О.Н.; Головкова, М. Е.; Уварова, И.В. (2009)
The problem of transformation of iron powders under the action of the main components of tissue fluid has been studied. It was established that, in order to model the process of interaction of iron powder with tissue fluid in vitro, the solution consisting of human blood plasma and the 0.9% physiological one with relationship 1 : 1 should be used as a model medium. The process of the biotransformation of iron powder which takes place here is similar to the natural process in living organism. It was shown to proceed more rapidly than the process of corrosion. It was also established that sprayed iron powders are more attackable under the action of water and a model medium than carbonyl iron powders.